A dialética sujeição/emancipação: elementos para uma Teoria Crítica das Tecnologias Digitais - Melo, Marco César de Souza (2023)
The present research aims to analyze the relationship between subjection and resistance/emancipation from the essayistic elaboration of a critical theory of digital technologies. As a main theoretical reference, we start from the work of the American/Canadian thinker Andrew Feenberg, who, while moving through the philosophy of technique and critical theory, produced a critical theory of technology, which he later named critical constructivism.The central concepts worked by this philosopher are technical code and subversive rationalization. With these categories, the author thinks, respectively, the production and appropriation of technologies in contemporary capitalist society. For him, the technical code refers to the set of guidelines that direct the production of artifacts and tools, while the subversive rationalization refers to the capacity of appropriation and free use of these same artifacts by users, which often even results in modifications of the codes. In this sense, Feenberg believes in the existence of a trend within the very dynamics of technologies that points to a democratic use of them. We will take Feenberg's ideas as a reference, but we intend to rehearse a critical theory of digital technologies. We believe it is necessary to fill some gaps that Feenberg's analysis leaves open: the potential use of digital technologies for the consolidation of new forms of control. To study this data we will bring as references Tim Wu, Manuel Castells, Byung-Chul Han and other researchers who analyze the new digital technologies and the network society with their specific problems. To conclude we will propose a discussion about the category of Feenbergian subversive rationalization and Wu's cyclical thinking. Such discussion focuses on analyzing the possibilities of dismantling the interest of corporate monopolies in cyberspace. We aim to verify a possible dialectical tension between the forces of domination and those of resistance in today's technological society. By re-reading Feenberg's concepts and analyzing the aspects related to digital technologies, we question whether it is possible to nod in the direction of a critical theory of digital technologies.